(untitled) (Scientific journal of the Fergana State University, 2024)
The article discusses topical issues of using the institute of complaints as one of the key mechanisms for protecting the rights of participants at the pre-trial stage of the criminal process. The author analyzes the legal regulation of filing and consideration of complaints, as well as their role in ensuring legality and fairness at the stage of preliminary investigation and inquiry. Special attention is paid to the effectiveness of this institution in the context of ensuring the procedural rights of both accused and suspects, as well as victims. The article also discusses the problems that arise in the exercise of the right to file a complaint, and suggests possible solutions to improve law enforcement practice.